Infilling in German cities. Analysing the extent and spatial distribution of infilling and its effects on housing density between 1991 and 2011 - Eichhorn, Sebastian (ERDKUNDE, 2024)
Infilling is considered one of the most important planning principles worldwide to reduce urban growth and urban sprawl. This also applies to Germany. However, due to a lack of nationwide small-scale data, there are hardly any empirical findings on how infilling has taken place in German cities. Using a newly developed GIS-based algorithm and small-scale data on residential construction activity (100x100m grid cells) and built-up areas, we analyse how residential development has evolved in 30 German case studies over a study period from 1991 to 2011. Within concentric 1km rings, our analysis differentiates residential construction activity by infilling, building types, land cover and housing density. Using cluster analysis, we further group the case studies into more homogeneous groups. The findings show that infilling has been pursued and implemented by most of the case studies since the 1990s. However, it becomes clear that there are large differences in the extent of infilling and that it does not necessarily lead to an increase in housing density. The findings show - in addition to national regulations and guidelines as well as population development - that it is primarily the structural framework conditions, the specific commitment of the municipalities as well as local and regional challenges that determine the type of residential construction activity.